MAKING EXCELLENCE A HABIT FOR CONTINUED SUCCESS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, November 2015 – The whole Universiti Sains Malaysia (USM) community has been called upon to increase productivity and strive for future successes in the future.